Legal Protection Mechanisms and Consequences for Medical Negligence in Healthcare Services: Mekanisme Perlindungan Hukum dan Konsekuensi atas Kelalaian Medis dalam Pelayanan Kesehatan - Njoto, Harsono (Rechtsidee, 2023)
This study critically examines the role of legal safeguards in enhancing healthcare service quality. Utilizing normative legal research methods, the study employs legislative and conceptual approaches to explore the dual nature of legal protection: preventive and repressive, in the context of healthcare professionals adhering to established Standard Operating Procedures (SOPs). The findings suggest that healthcare practitioners' negligence level and the resultant harm to patients or the public determines the legal implications. Such implications range from allegations of SOP and ethical code violations, to civil litigation for damages, and even criminal charges if medical actions endanger lives, potentially causing patient mortality. Therefore, the study highlights the necessity for legal accountability for healthcare practitioners, emphasizing that their service delivery must align with the set SOPs. These findings have profound implications for policy-making, emphasizing the need for robust legal protection for both healthcare practitioners and service recipients, thereby ensuring improved healthcare service quality.Highlights: Dual nature of legal protection in healthcare. Negligence level dictates legal consequences. Emphasis on healthcare practitioners' legal accountability. Keywords: Legal Protection, Healthcare Services, Medical Negligence, Standard Operating Procedures, Legal Consequences